Peripheral blood cytogenetics allows treatment monitoring and early identification of treatment failure to lenalidomide in MDS patients: results of the LE-MON-5 trial - Braulke, Friederike; Nolte, Florian; Hofmann, Wolf-Karsten; Schlenk, Richard Friedrich (Annals of hematology, 2017)
Transfusion-dependent patients with low- or intermediate-1-risk myelodysplastic syndrome, <5% bone marrow (BM) blasts and isolated 5q-deletion received lenalidomide within the German MDS study group phase-II clinical trial LE-MON-5 (EudraCT:2008-001866-10) of the University of Duesseldorf, Germany. Cytogenetic monitoring was performed by chromosome banding analyses (CBA) of BM cells and fluorescence in situ hybridization (FISH) analyses of peripheral blood (PB) mononuclear CD34+ cells using extended probe panels. Out of 144 patients screened for study enrollment, 24% failed to meet inclusion criteria due to cytogenetic findings. Eighty-seven patients were followed with a median observation time of 30 months. Cytogenetic response detected by FISH and CBA in 74 and 66% of patients, respectively, was predictive for hematologic response as well as of high prognostic relevance. After 2 years, AML rate was 8% for all patients. Karyotype evolution was detected in 21 (FISH)-34% (CBA) of patients associated with significantly shorter AML-free survival. Disease progression was first detectable on the cytogenetic level on average 5-6 months before recurrence of transfusion dependence. Our data show for the first time in a prospective setting that a cytogenetic monitoring from the PB helps to early identify treatment failure and progressive disease in lenalidomide-treated patients to improve clinical management. Trial registration: EudraCT:2008-001866-10
First online: 03 April 2017
Gesehen am 19.06.2018